Increasing the known specific richness of living mammals in Chile - Quiroga-Carmona, Marcial; González, Alex; Valladares, Pablo; Hurtado, Natalí; Dâ€™Elía, Guillermo (THERYA, 2022)
The Chilean mammal fauna is one of the best known of South America. In spite of this, in the last decade several new species have been described based on specimens collected in the country, while other species previously known elsewhere have been recorded for the first time in Chile. Here we keep on this trend by recording for the first time for Chile a species of long-tailed mouse of the genus Oligoryzomys. This mention is based on genetic (cytochrome b gene sequences) and morphological data gathered from several specimens collected at four localities of Quebrada de Camarones, Región de Arica y Parinacota in northern Chile. At one of these localities a specimen was live-trapped; while in the other three localities several osteological remains were recovered from owl pellets. The morphologic and genetic information robustly indicate that the revised specimens belong to the genus Oligoryzomys. The phylogenetic analyses show that the trapped specimens belong to O. flavescens s. l. However, it remains unsolved to which of two main lineages of O. flavescens s. l., O. flavescens s. s. or O. occidentalis, belongs the specimens from Camarones. Here we increase the known species richness of Chilean living mammals by showing that northernmost Chile is inhabited by O. flavescens s. l. The possibility that the specimens from Camarones represent an undescribed species cannot be ruled out. These new records indicate, once again, that much remains to be learn about basic aspects of the Chilean mammals, including which species form the local assemblages.